Middle School Teachers' Perceptions of the Merdeka Mengajar Platform as a Source of Independent Learning - Nofianti; Deni Hardianto; Pujiriyanto (Postgraduate, University of Mataram, 2025)
This study aims to examine junior high school teachers' perceptions of the Merdeka Teaching Platform (PMM) as an independent learning resource. The research method used is a survey with a descriptive approach. Data were collected through questionnaires and limited interviews. The research subjects were 21 general subject teachers at SMP VIP Pesawat Wates, Kulon Progo. The results showed that most teachers understood the concept and purpose of PMM, but many had not optimally utilized its features. The level of teacher satisfaction with PMM features is high, but there are still some teachers who feel less satisfied. The majority of teachers have used PMM as an independent learning resource, but there are still some who are less independent. Support and facilities provided by schools for PMM utilization are still not fully met. The discussion shows that PMM has not been fully utilized by teachers as an independent learning resource. This is due to several factors, such as teachers' lack of understanding about PMM, lack of support and facilities from the school, and teachers' lack of motivation and awareness to learn independently. In conclusion, PMM has not been fully utilized by junior high school teachers as an independent learning resource. Efforts are needed to improve teachers' understanding of PMM, provide adequate support and facilities, and motivate teachers to learn independently.